Efectos de dos protocolos de potenciación post-activación sobre el rendimiento en el salto vertical, en relación al perfil f-v en jugadoras de balonmano de élite - Sanchez-Lopez, S.; Rodriguez-Perez, M. A. (Revista Ciencia del Deporte, 2018)
Aim: To know the effects of two protocols of Post-Activation Potentiation (PAP) on the performance in a Countermovement Jump (CMJ) and its relationship with the Force-Velocity Profile (Profile F-V). Methodology: Repetition Maximum (RM) was evaluated in the squat exercise, and the FV Profile of 9 handball players of Silver Honor Division (age, 21.3 ± 3.4 years, height, 167.9 ± 5, 82 cm, and weight, 66.51 ± 9.6 kg). Subsequently, two PAP protocols were performed, with different intensities (3x3 65% RM and 3x3 80% RM), to check effects on the CMJ at different recovery times (15s / 4/8/16/24 min). Results: The protocol of 3x3 to 65% RM suffered a decrease at 15s of 15.03% with respect to the PREtest, achieving the best mark at 8min, but being 4.5% lower than the PREtest. After the 3x3 to 80% RM, the jump again suffered a decline at 15s, this time of 11.61%, getting the best mark at 4 and 16min, this being 6.5% lower than the PREtest. The relationship between the jump to the 15s and the imbalance of the FV Profile (FVimb) with the protocol of 3x3 to 80% RM, puts into play 22% of common elements (rs = 0.467, r2 = 0.22), while that with the protocol of 3x3 to 65% RM only puts at stake 8% (rs = 0.283, r2 = 0.08). Conclusions: The protocols used suppose an excessive stimulus for this type of subjects on the CMJ, which seems to be related to the FVimb that they present.